A mixed-methods exploration into the resilience of community drug distributors conducting mass drug administration for preventive chemotherapy of lymphatic filariasis and onchocerciasis in Côte d'Ivoire and Uganda - Daniel Dilliott; David Addiss; Charles Thickstun; Adam Mama Djima; Esther Comoe; Lakwo Thompson; Stella Neema; Mary Amuyunzu-Nyamongo; Amos Wung-Buh; Deborah McFarland; Margaret Gyapong; Alison Krentel (Public Library of Science (PLoS), 2022)
Volunteer community drug distributors (CDDs) have been vital to progress made in the elimination of onchocerciasis and lymphatic filariasis; two neglected tropical diseases amenable to preventive chemotherapy (PC-NTDs). However, formative work in Côte d'Ivoire and Uganda revealed that CDDs can encounter considerable challenges during mass drug administration (MDA). CDDs must be resilient to overcome these challenges, yet little is known about their resilience. This mixed-methods study explored the resilience of CDDs in Côte d'Ivoire and Uganda. The characteristics and experiences of 248 CDDs involved in the 2018 MDAs in Côte d'Ivoire (N = 132) and Uganda (N = 116) were assessed using a micronarrative survey. Thematic analysis of CDDs' micronarratives was used to identify challenges they encountered during MDA. Resilience was assessed using the Connor-Davidson Resilience Scale 25 (CD-RISC-25). Variables from the micronarrative survey found to be individually associated with mean CD-RISC-25 score (P<0.05) through bivariate analyses were included in a multiple linear regression model. Post-hoc, country-specific analyses were then conducted. Thematic analysis showed that CDDs encountered a wide range of challenges during MDA. The aggregate model revealed that CDDs who had positive relationships or received support from their communities scored higher on the CD-RISC-25 on average (P<0.001 for both), indicating higher resilience. These trends were also observed in the country-specific analyses. Mean CD-RISC-25 scores were unaffected by variations in district, age, gender, and length of involvement with the NTD program. Community support during MDA and positive community-CDD relationships appear to be associated with CDDs' personal capacity to overcome adversity. Involving communities and community leadership in the selection and support of CDDs has the potential to benefit their well-being. This study establishes the CD-RISC-25 as a useful tool for assessing the resilience of CDDs. Further research is needed to understand, promote, and support the resilience of this valuable health workforce, upon which NTD programs depend.